Muhammad Mansur Yafi ANALISIS PROSES PADA PELAYANAN RUMAH SAKIT DI JAWA TIMUR: Program Studi Teknik Industri, Universitas Nahdlatul Ulama Sidoarjo, Sidoarjo *e-mail: yafimansur@gmail.com - Muhammad Mansur Yafi (GREENOMIKA, 2019)
The hospital has improved the information system so that it can improve properly to improve patient satisfaction and the quality of its services. However, complicated characteristics such as hospitals are very complicated. in this study, evaluating the results of a complex analysis of hospital processes. To compare the complexity of the old process and the new process, the Business Process Modeling and Notation (BPMN) standard is used. The results showed that the repair process could be used for the hospital repair process.